Analysis on the Characteristics of Crustal Structure and Seismotectonic Environment in Zigui Basin, Three Gorges - Wu, Yunlong; Pei, Junling; Wang, Ze; Zhang, Yi; Yuan, Huaqing (Frontiers in Earth Science, 2021)
The Zigui Basin in the Three Gorges area is a syncline running in the north-south axial direction; the sediments in the basin are mainly late Triassic-late Jurassic sandy and argillaceous rocks. Since the Three Gorges Project began undergoing impoundment in May 2003, nearly 20,000 mini-earthquakes have occurred in the Zigui–Badong region, including five earthquakes with magnitudes greater than Ms 5.0. Herein, a 3D gravity inversion method was introduced to investigate the density structure of the Zigui Basin and its adjacent areas. A comprehensive analysis of the geological structure of the area was carried out, based on focal mechanism solutions of six moderate–strong earthquakes in the area. The Zigui Basin is a low–density area from the periphery, and the sediment in the east is thicker but less dense than in the west. The shallow part of the Zigui Basin is a weak bottom layer prone to slippage, and the deep part (5–10 km) could comprise lithological strata such as limestone, sandstone, and shale, which easily undergo dissolution by leaking reservoir water. Under the action of external forces such as long-term infiltration and unloading of reservoir water, fissures will expand and squeeze then earthquakes are likely induced in the deep strata. Furthermore, new buried faults in the western and southeastern edges of the core area of the Zigui Basin could also trigger an earthquake under long–term pressurization and reservoir water penetration.